The Optical Aspect of Errors in Measurements of Surface Asperities Using the Optical Profilometry Method - Grochalski, Karol; Wieczorowski, Michał; H'Roura, Jihad; Le Goic, Gaetan (Frontiers in Mechanical Engineering, 2020)
The paper presents the impact of lighting type and direction on measurements of surface asperities using a focus - variation microscopy. Particular attention was paid to the direction of lighting used using a light ring. It was pointed out that the lighting direction directly affects the values of the parameters Rt, Rz and Rc. The article also presents the impact of a light polarizer on the surface topography parameters obtained. It has been shown that the positioning of a sample with a regular and directed structure relative to the optical axis of the light polarizer affects the accuracy of mapping surface asperities. The largest differences were observed for Rz and Rt parameters. A method of using an external polarizer mounted on a focus variation microscope lens was also presented.